Papillon-Lefevre syndrome, Genetic aspects of host susceptibility & treatment modalities- A case report - Rad Afshar G. (Tehran University of Medical Sciences, 2002)
Diagnosis and treatment of patients with periodontitis as a manifestation of systemic diseases"nis of especial concern to the periodontist, especially those associated with genetic disorders, which have"npoor prognosis. With aggressive progression of periodontal bone and attachment loss, a patient could be"na partial or total edentulous early in life."nThe aim of this article was to report a case of Papillon-Lefevre syndrome (PLS) with generalized"nprepubertal periodontitis (GPPP). A ten-year old boy for whom active periodontal treatment and"nsubsequent maintenance recalls was performed for five years since the diagnosis of PLS. Treatment"nprocedures included: precise mechanical instrumentation at several visits, periodontal surgery, adjunctive"nserial systemic antibiotic therapy, professional irrigation of pockets with 0/2% chlorhexidine solution and"nperiodic maintenance recall visits. In spite of all of these, progressive course of the disease continued"nuntil the patient was fifteen and edentulous. Unfortunately association of GPPP with systemic"nunmanageable condition or diseases has caused refractory periodontitis, which yet has no proven and"nreliable treatment protocol. Besides, this article has discussed more successful treatment modalities for"nPLS with GPPP and the genetic aspects of host susceptibility, which is a complicated and challenging"nfield.